Proceedings of the Ninth International Workshop on Data Management on New Hardware 2013
DOI: 10.1145/2485278.2485285
|View full text |Cite
|
Sign up to set email alerts
|

Enabling efficient OS paging for main-memory OLTP databases

Abstract: Even though main memory is becoming large enough to fit most OLTP databases, it may not always be the best option. OLTP workloads typically exhibit skewed access patterns where some records are hot (frequently accessed) but many records are cold (infrequently or never accessed). Therefore, it is more economical to store the coldest records on a fast secondary storage device such as a solid-state disk. However, main-memory DBMS have no knowledge of secondary storage, while traditional disk-based databases, desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Data overflow. In general, approaches to the data overflow problem can be classified into three categories: user-space (e.g., H-Store Anti-caching [133], Hekaton Siberia [134]), kernel-space (e.g., OS Swap, MongoDB memory mapped files [65]) and the hybrid (e.g., Efficient OS Paging [136] and UVMM [138]). The semantics-aware user-space approaches can make more effective decision on the paging strategies, while the hardware-conscious and well-developed kernel-space approaches are able to utilize the I/O efficiency brought by the OS during swapping.…”
Section: Research Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Data overflow. In general, approaches to the data overflow problem can be classified into three categories: user-space (e.g., H-Store Anti-caching [133], Hekaton Siberia [134]), kernel-space (e.g., OS Swap, MongoDB memory mapped files [65]) and the hybrid (e.g., Efficient OS Paging [136] and UVMM [138]). The semantics-aware user-space approaches can make more effective decision on the paging strategies, while the hardware-conscious and well-developed kernel-space approaches are able to utilize the I/O efficiency brought by the OS during swapping.…”
Section: Research Opportunitiesmentioning
confidence: 99%
“…The semantics-aware user-space approaches can make more effective decision on the paging strategies, while the hardware-conscious and well-developed kernel-space approaches are able to utilize the I/O efficiency brought by the OS during swapping. Potentially, both the semantics-aware paging strategy and hardware-conscious I/O management can be exploited to boost the performance [136], [138]. In addition to the above, hardware solutions are being increasingly exploited for performance gain.…”
Section: Research Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stoica and Ailamaki profiled the performance of the stateof-the-art in-memory VoltDB database, and found that performance dropped precipitously when the working data set exceeded available memory [37]. Their work demonstrated that by intelligently controlling which tuples are swapped out by the operating system and which are kept in memory, it is possible to make much more effective use of available memory.…”
Section: In-memory Database Systemsmentioning
confidence: 99%
“…Unfortunately, there are no mechanisms for asynchronous read-ahead and for writing multiple pages concurrently, i.e., multiple msync calls execute serially. As observed by [37], without extensive explicit control, the virtual memory manager may swap out hot data along with the cold. Our experiments in Section 5 demonstrate this performance penalty.…”
Section: Virtual Memorymentioning
confidence: 99%